2021
DOI: 10.3390/diagnostics11091697
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Therapeutic Response Markers for Acupuncture in Parkinson’s Disease: An Exploratory Pilot Study

Abstract: In this preliminary pilot study, we investigated the specific genes implicated in the therapeutic response to acupuncture in patients with Parkinson’s disease (PD). Transcriptome alterations following acupuncture in blood samples collected during our previous clinical trial were analyzed along with the clinical data of six patients with PD, of which a representative patient was selected for transcriptomic analysis following acupuncture. We also examined the changes in the expression of PD biomarker genes known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several studies on the post-mortem brain of PD also suggested SYN1 as one of the PD biomarkers [ 118 , 119 , 120 ]. Among them, SYN1 and ANKRD22 were proposed as therapeutic response markers in blood samples of PD [ 121 ]. Additionally, the pathogenesis of PD, such as dysregulation of mitochondria, the ubiquitin–proteasome system, metabolism, and oxidative system, was captured in the transcriptome signature from the blood of patients with PD [ 122 ].…”
Section: Classification Of Pdmentioning
confidence: 99%
“…Several studies on the post-mortem brain of PD also suggested SYN1 as one of the PD biomarkers [ 118 , 119 , 120 ]. Among them, SYN1 and ANKRD22 were proposed as therapeutic response markers in blood samples of PD [ 121 ]. Additionally, the pathogenesis of PD, such as dysregulation of mitochondria, the ubiquitin–proteasome system, metabolism, and oxidative system, was captured in the transcriptome signature from the blood of patients with PD [ 122 ].…”
Section: Classification Of Pdmentioning
confidence: 99%
“…The GEO database at (https://www.ncbi.nlm.nih.gov/) was searched with the keyword "Acupuncture Parkinson's Disease" at, and the human species was selected to obtain the transcriptomic data of acupuncture for Parkinson's disease. Transcriptomic data of Parkinson's patients were obtained from [12], and their associated GSE178470 matrix and platform files were downloaded and saved as Excel datasheets, the obtained data were organized and summarized. By taking the mean and logarithm, the data with different change trends after 5 and 8 treatment sessions were removed, and the targets with |log2FC| > 1 were screened as potential targets of acupuncture action.…”
Section: Acupuncture For Parkinson's Disease Potential Targetsmentioning
confidence: 99%
“…Acupuncture, originating from “acupuncture stones,” is the essence of traditional Chinese medicine and is recognized as a natural treatment without annoying side effects. Acupuncture plays a conspicuous role in the therapy of PD, which not only improves motor symptoms such as tremors and shuffling but also effectively relieves non-motor symptoms such as constipation, depression, and insomnia [ [3] , [4] , [5] ]. However, it remains unclear about the mechanism underlying the effect of electroacupuncture (EA) in PD.…”
Section: Introductionmentioning
confidence: 99%